Desenvolvimento das raízes tuberosas em mandioca (Manihot esculenta Crantz) - Cavalcanti, Josias (1985)
A field study was carried out in Pacajus-Ceará-Brasil, in order to study the development of tuber roots of 6 cassava cultivars (Manihot esculenta Crantz). [...]